Preliminary determination of microplastics in bivalves collected from Phu Yen, central Viet Nam - Tran Thi Ai My; Nguyen Duy Dat; Nguyen Quoc Hung; Duong Tuan Quang (Vietnam Journal of Science and Technology, 2023)
In this study, four common bivalves (including Meretrix lusoria (clam), Anadara subcrenata (ark clam), Crassostrea gigas (oyster), and Perna viridi (green mussels)), which are more popularly consumed were collected from a fishery market in Phu Yen, Central Vietnam to investigate the occurrence of microplastics (MPs) in their tissues. Samples weretreated with a KOH solution of 10 % for 48 hours and incubated at 40 °C. The base-sample ratio was 10:1 v:w (i.e 10 mL of 10 % KOH solution per 1.0 gram of a tissue sample). The treatment followed by sodium iodide-based extraction was set as the protocol for the separation of MPs from biological materials. The number of MP items determined in clam, ark clam, oyster, and green mussels registered by weight and individual were 0.3 ± 0.1, 0.2 ± 0.2, 0.3 ± 0.1, and 0.5 ± 0.3(item/g-ww), and 1,4 ± 0.8, 1.5 ± 1.4, 3.0 ± 2.4, 2.3 ± 1.2 (items/individual), respectively. Fiber is the common shape (69-92% of total items), followed by fragment. Furthermore, Polyethylene terephthalate was confirmed as the polymer of the common fiber MPs found in collected samples. As the first investigation on MPs in bivalve tissue from Phu Yen, Central Vietnam, this study indicated that a relatively high level of MPs was found in the commercial bivalves collected from fishery market of Central Vietnam, warning a potentially high risk of human consuming bivalves as daily food is posed. Keywords: microplastics, bivalves, Phu Yen, Central Vietnam. Classification numbers: 3.2.1, 3.6.1.